A novel homozygous variant in C1QBP causes severe IUGR, edema, and cardiomyopathy in two fetuses. Issue 1 (5th March 2021) - Alstrup, Morten; Vogel, Ida; Sandager, Puk; Blechingberg, Jenny; Becher, Naja; Østergaard, Elsebet
Abstract: The C1QBP protein (complement component 1 Q subcomponent‐binding protein), encoded by the C1QBP gene, is a multifunctional protein predominantly localized in the mitochondrial matrix. Biallelic variants have previously been shown to give rise to combined respiratory‐chain deficiencies with variable phenotypic presentation, severity, and age at onset, from intrauterine with a mostly lethal course, to a late‐onset mild myopathy. We present two fetuses, one male and one female, of first‐cousin parents, with severe intrauterine growth retardation, oligo/anhydramnios, edema, and cardiomyopathy as the most prominent prenatal symptoms. Both fetuses showed no copy number variants by chromosome microarray analysis. Analysis of a fibroblast culture from one of the fetuses showed deficiency of respiratory chain complex IV, and using exome sequencing, we identified homozygosity for a novel variant in C1QBP in both fetuses. To our knowledge, only six patients with pathogenic variants in C1QBP have been reported previously and with this report, we add a novel pathogenic variant in C1QBP found in two related fetuses.